Experimental investigation of the adhesion regime transition in peeling - Low, Deon Shao Wei (Nanyang Technological University, 2024)
Peeling of adhesives is very common both in nature and in industries. Depending on geometry, modulus and adhesion parameters, the adhesion regime may be JKR-like with stress concentrated at the crack front or DMT-like with stress distributed uniformly. The Adhesion regime plays an important role both in determining and designing the adhesion strength of adhesives and in measuring the adhesive parameters. Adhesion regime in pulling mode is systematically investigated and validated both theoretically and experimentally. Despite many efforts in investigating the adhesion regime transition in peeling, there is still lack of systematic experimental validation covering the full transition range from JKR-like regime to DMT-like regime. Therefore, experimental results are needed to validate the results and findings done by previous researchers. Here, systematic experiments were conducted to validate the theory of the adhesion regime transition to include full range of JKR-like, transitional and DMT-like regimes. A peeling adhesion test platform, that can measure the maximum force needed to peel the tape off the glass substrate and the critical energy release rate during stable peeling, was firstly designed and constructed. The components to construct this adhesion test platform were either purchased or self-fabricated, then assembled onto an Instron 5566 Universal Testing Machine. After the platform was constructed, it was validated by running a peeling test with a regular single sided Polyimide tape and comparing the results with those from another research paper. After the validation was completed, peeling tape samples with different bending stiffness value were prepared. First, one side of the double-sided polyimide tape was sticked onto the backing material (polyimide film and steel) and cut into the desired geometry. Next, the other side of the double-sided polyimide tape was sticked onto the glass substrate. Roller was used to roll over the sample to ensure that constant pressure was applied throughout the sample. After sample preparation process, the samples were subjected to 90 degrees peeling test and the force versus displacement curves were obtained then analysed and categorised into JKR, transition or DMT regime based on the characteristics of the curve. Analysis such as maximum force versus bending stiffness was also conducted. It was shown that the maximum peeling force can be fitted as a function of the bending stiffness of the tape as P = [1 + ^(10.93+2.644× 10 )] − [1 + ^(10.259+2.644× 10 )] + 0.330, which validated the full- scale adhesion regime transition in peeling. The results of this thesis can serve as both the experimental validation and the design guideline for peeling adhesion transition phenomenon.